PENGARUH AUDIT KINERJA TERHADAP PENINGKATAN KINERJA KEUANGAN PDAM TIRTA PAKUAN KOTA BOGOR - Chandra Pribadi; Maestro Giovani (JIMFE (Jurnal Ilmiah Manajemen Fakultas Ekonomi), 2018)
ABSTRACTThere is also the author of the type of research used in this paper is descriptive ekploratif, with case study research method and technique of quantitative and qualitative research dekriptif (non statistical). To obtain the necessary data and information, the authors conducted a study in PDAM Tirta Pakuan Kota Bogor, Finance Division, Internal Audit Division, Transmission and Distribution Division. Implementation of performance audit PDAM tirta Pakuan Kota Bogor set forth in the statements of performance, particularly on the description of the performance evaluation results of the companys development. Performance audit is comprised of four stages, namely the audit planning, audit execution, audir reporting the results of monitoring the implementation of the recommendations for improvement. Performance audit conducted by the satuan pengawasan intern. Costs other than authorized and controlled by the management unit it self, in its implementation are also given supervision. Oversight is conducted by the satuan pengawasan intern in order to achieve the performance audit objectives, namely t improve water supply services to the community both in quatity and quality, and to find success in managing the company:s directors. Based on these problems, it can be concluded that the implementation of the performance audit conducted on the mechanism of internal auditors in helping to oversee the management of cost control, especially the cost or transmission and distribution clout to improve the financial performance of the PDAM Tirta Pakuan Kota Bogor.Key word: Performance Audit,Financial Performance Improvement